Prognostic factors affecting outcome of hospitalised infants 1-6 months with severe acute malnutrition in North India - Kumar, Lalit; Das, Ghanshyam; Gaur, Ajay (International Journal of Contemporary Pediatrics, 2018)
Background: Emerging evidences show that severe acute malnutrition is prevalent in infants below 6 months of age. This study is focused on the prognostic factors which decide the outcome of management of these infants in a hospital. Methods: Admitted patient for severe acute malnutrition and related complications were observed during their stay in the hospital. Detailed history to find out contributing factors that cause severer acute malnutrition in this age group was taken. Anthropometry, related morbidities were recorded and outcome was assessed. Results: A total of 115 infants of 1 to 6months of age were enrolled to study. Birth characteristics such as birth weight (p-value 0.0133), prematurity (p-value 0.023), birth spacing (p-value 0.0064), infant feeding characteristics as giving pre-lacteal feed(p-value 0.011), exclusive breast feeding (p-value 0.0473), deprivation of colostrum (p-value 0.003), maternal characteristics as age at first conception (p-value <0.0001), maternal literacy status ( p-value 0.0453); presence of sepsis, incomplete immunization, presence of bilateral pedal edema, visible severe wasting, all these variables were found to affect the recovery of an infant during hospital stay. Conclusions: The present study helps to identify significant risk factors associated with severe acute malnutrition in less than 6 months old infants which can be included in management, prevention and policy making in future.